Epidemiological, Clinical and Paraclinical Characteristics of Childhood Acute Lymphoblastic Leukaemia in Sana'a, Yemen - Mohammed Ali Al-Shehab; Abdulrahman Mohammed Alhadi; Muna Abdo M. Elnemr; Farouk Abdulrahman Al-Qadasi; Naseem Abdo Alabsi; Mohammed Abdo Aqlan (JCDR Research and Publications Private Limited, India, 2020)
Introduction: Acute leukaemia is one of the most common types of cancers among children. There is only restricted number of studies about childhood leukaemia in Yemen, hence the importance of performing this study. Aim: To assess the epidemiological, clinical and para-clinical characteristics of childhood acute lymphoblastic leukaemia in Sana'a, Yemen. Materials and Methods: This was a descriptive retrospective study. It included 177 children younger than 15 years with Acute Lymphoblastic Leukaemia (ALL), who were diagnosed in the period from May to September 2011 to 2017 in the Childhood Leukemia Management Center (CLMC) in Sana’a, Yemen. The diagnosis was based on clinical characteristics, bone marrow morphology and immunophenotyping. The data was analysed using SPSS program. Chi-square test with Yate correction and Fisher tests were used to identify the significance of associations. Results: Majority of patients 129 (72.8%) were between 1-9 years and male to female ratio was 1.53 to 1. The most common presenting features were fever (89.3%), pallor (89.3%) and bone pain (71.3%). Immunophenotyping was done for 126 patients; 99 (78.6%) had precursor B-cell and 27 (21.4%) had T-cell ALL. Ninety two (52.6%) of patients were classified as standard risk and 83 (47.4%) were high risk; most of them were T-cell ALL. Response to chemotherapy in induction phase was excellent with complete remission rate of 94.2%. Relapse was 16.5%; 62.9% of them were medullary relapses. Mortality during induction was 15.6%. Infection was the most common cause of death (37.8%), followed by haemorrhage (11.1%). Conclusion: ALL is considered a significant health problem in Yemen. It needs high awareness and more attention from the governorate regarding improving the capacities of health facilities on health information, diagnosis and treatment.